ANALISIS PELAKSANAAN KEBIJAKAN PENATAAN PEMASANGAN REKLAME LUAR RUANGAN DI KOTA PEKANBARU - Wildasari Siregar; Dia Meirina Suri (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2018)
The research is based on the principal issues concerning the billboard planning policy which has not optimally be able to improve the loca revenue of Pekanbaru City an has not improved the beauty of Pekanbaru City . It was estimated to be caused by the model of the billboard planning policy can not increase the billboard tax receipts as well as to enhance the visual beauty of Pekanbaru City. The method used in this research is descriptive quantative, which be able to improve the billboard tax planning policy implementation which be able to billboard tax receipts and to enhance the visual beauty of Pekanbaru City. The collection of data is used, as is common in quantitave research are observation, interviews and documentation. The research result indicated that (1) the billboard planning policy implementation running in the Pekanbaru City still not effective because of lack of attention to standards and palicy objevtives and amplementing organizational characteristic are also not proved the role in billboard planning policy implementation in Pekanbaru City .(2) the model of billboard planning policy implementation of Pekanbarun City mandated the regional revenue office of Pekanbaru City as the responsible agency for organizing and billboard planning in Pekanbaru City.